ESTIMASI SISA NASI KONSUMEN DI BEBERAPA JENIS RUMAH MAKAN DI KOTA BOGOR - Dini Anriany; Drajat Martianto (Jurnal Gizi dan Pangan, 2013)
This study aimed to estimate waste of cooked rice not consumed by customer at various restaurants in Bogor. Cross sectional study design was implemented in this study. The number of subjects were 279 consumers from 32 restaurants. Food weighing method was used to measure cooked rice waste and the weight was then converted into rice weight using a conversion factor. The calculations show that rice loss from sunda restaurant was the highest with an average of 4.7 g/capita/day of rice equivalent, while the smallest in padang restaurant with the average of 2.5 g/capita/day of rice equivalent. For java and warung tenda restaurant were equal to 3.6 g/capita/day of rice equivalent and 4.2 g/capita/day of rice equivalent. Respectively loss of nutrients per meal from sunda restaurant was equal to 8.3 kcal/capita (0.4% of energy RDA), 0.1 g/capita (0.2% of the protein RDA). While the loss of nutrients from padang restaurant was as much as 4.5 kcal/capita (0.2% of energy RDA), 0.05 g/capita (0.1% of the protein RDA). Loss of nutrients from java restaurant was 6.3 kcal/capita (0.3% of energy RDA), 0.07 g/capita (0.1% of the protein RDA). For warung tenda, loss of nutrients was 7.5 kcal/capita (0.4% of energy RDA), 0.09 g/capita (0.2% of the protein RDA). It seems that the loss of the waste of the rice on sunda restaurant by serving in a bakul, has not been able to reduce of rice waste.